2020
DOI: 10.1186/s40478-020-00939-0
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional analyses of adult and pediatric adamantinomatous craniopharyngioma reveals similar expression signatures regarding potential therapeutic targets

Abstract: Adamantinomatous craniopharyngioma (ACP) is a biologically benign but clinically aggressive lesion that has a significant impact on quality of life. The incidence of the disease has a bimodal distribution, with peaks occurring in children and older adults. Our group previously published the results of a transcriptome analysis of pediatric ACPs that identified several genes that were consistently overexpressed relative to other pediatric brain tumors and normal tissue. We now present the results of a transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…According to the theory of embryogenesis, CP may occur anywhere in the migration of Rathke's sac ( 1 ), such as the nasopharynx, paranasal sinus, third ventricle, and posterior cranial fossa ( 2 , 3 ). Still, it can also occur in the suprasellar cistern ( 4 ), temporal lobe ( 5 ), and cavernous sinus ( 6 ). This kind of ACP involving the anterior, middle, and posterior cranial fossa of adults is rarely reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…According to the theory of embryogenesis, CP may occur anywhere in the migration of Rathke's sac ( 1 ), such as the nasopharynx, paranasal sinus, third ventricle, and posterior cranial fossa ( 2 , 3 ). Still, it can also occur in the suprasellar cistern ( 4 ), temporal lobe ( 5 ), and cavernous sinus ( 6 ). This kind of ACP involving the anterior, middle, and posterior cranial fossa of adults is rarely reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent gene expression data indicate that therapeutic targets identified in pediatric ACP may also have relevance in adult ACP. 16 Thus, further investigations with larger patient numbers and additional agents are merited.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the latter classification does not clarify the relationship between different subtypes and dysregulated pathways. [18–20] Although heterogeneity is also significant among ACPs' transcriptome profiles in Prince et al 's [29] study, these authors failed to identify any differences between children and adults. However, a study of pediatric brain tumors identified two subtypes, "epithelial" and "immune hot," in ACPs by proteomics and phosphorylated proteomics data.…”
Section: Introductionmentioning
confidence: 99%